The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s13197-017-2677-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of potato tubers: the effect of cultivars and growth conditions

Abstract: The aim of the study involved evaluating the chemical composition of tubers of five potato cultivars that were grown under the same cultural practices in soils with low, medium, and high availability of phosphorus. The experimental designs corresponded to a randomized block with four replicates. Tuber samples were analyzed in terms of moisture, ash, protein, lipid, total sugar, fiber, starch, and phosphorus contents. The results suggested that increased availability of phosphorus in soil allowed the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 34 publications
8
44
1
Order By: Relevance
“…The results of our present study found that the moisture and carbohydrate content of potato tubers was 80.34±0.59% and 13.39±0.18%. Similar data were observed by Leonel et al (2017), they revealed that the moisture of potato tubers in a range of 78.17 to 88.11%, which is influenced by the combination of soil P availability and cultivars. Puttongsiri et al (2012) reported the potato consisting of 63-83% moisture content, 13-30% carbohydrate.…”
Section: Moisture and Carbohydrate Content Of Potato Carrot Tomatosupporting
confidence: 86%
“…The results of our present study found that the moisture and carbohydrate content of potato tubers was 80.34±0.59% and 13.39±0.18%. Similar data were observed by Leonel et al (2017), they revealed that the moisture of potato tubers in a range of 78.17 to 88.11%, which is influenced by the combination of soil P availability and cultivars. Puttongsiri et al (2012) reported the potato consisting of 63-83% moisture content, 13-30% carbohydrate.…”
Section: Moisture and Carbohydrate Content Of Potato Carrot Tomatosupporting
confidence: 86%
“…High content of phosphorus in tubers can cause an increase in the amylose content and changed thermal and pasting starch properties [62]. In addition, it causes an increase in the dry matter, starch, and proteins contents, but decreases total sugar content [63]. Thus, phosphorus is extremely important in the proper development of potato tubers quality.…”
Section: Phosphorus Content In Tubersmentioning
confidence: 99%
“…This in turn leads to higher amylose content and changed thermal and pasting starch properties (Leonel et al 2016). A recent study confirmed that increased P availability in soils resulted in tubers with higher dry matter content, lower total sugar content, and higher contents of both starch and proteins (Leonel et al 2017). Therefore, P is extremely important in the optimal development of quality potato tubers.…”
Section: Phosphorous and Sulfurmentioning
confidence: 99%